2006
DOI: 10.1007/s00213-006-0574-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hetero- and homosexual experience and long-term treatment with fluoxetine on homosexual behavior in male rats

Abstract: Only long-term administration of FLX does not interfere with the homosexual behavior in male rats. The homosexual and the heterosexual experience facilitated the homosexual behavior on the control and experimental groups. We suggested that learning aspects related to sexual behavior are responsible by these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…During the observation, two 25-watt infrared lamps provided room illumination. The rats were accustomed for 15 days to the reversed light/dark cycle before beginning the sexual behavior studies [40,41] .…”
Section: Offspring Evaluationsmentioning
confidence: 99%
“…During the observation, two 25-watt infrared lamps provided room illumination. The rats were accustomed for 15 days to the reversed light/dark cycle before beginning the sexual behavior studies [40,41] .…”
Section: Offspring Evaluationsmentioning
confidence: 99%
“…Sexual experience improves sexual behavior by decreasing the first mount and first intromission latencies, which can be related to previous learning (Cruz-Casallas, Nasello, & Felício, 2000;Habr-Alencar et al, 2006;Tenk et al, 2009;Teodorov et al, 2002). However, parameters such as ejaculation latency, number of intromissions until ejaculation and post ejaculatory latency were not altered.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, earlier studies made by our group and others revealed that experience facilitates the male rat's heterosexual and homosexual behavior (Habr-Alencar, Dias, Teodorov, & Bernardi, 2006;Teodorov, Salzgeber, Felicio, Varolli, & Bernardi, 2002) and decreases or eliminates related impairments (Pfaus et al, 1995;Taylor et al, 1996). Some aspects of sexual function, such as mounts and intromissions, can be modified by sexual experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point of interest is that drugs that affect serotonin and norepinephrine may alter sexual orientation, although probably only to a very small degree if at all [12]. And mental illnesses such as depression and bipolar disorder may not only affect sexual potency, which is well established [13–15], but may also subtly affect sexual orientation.…”
mentioning
confidence: 99%